(untitled) (Journal of the College of Basic Education, 2023)
his study dealt with the topic of the letter that was attributed to Ibrahim Al-Imam, who is the family ofThe Abbasid call. The authors of the letter said: It was issued by him to Abu Muslim al-Khurasani.dated .... carries recommendations for the chief preacher revolving around the Abbasid da’waIt found a fertile climate in Khorasan, due to its distance from the center of the Caliphate. This is from one sideOn the other hand, the Arabs in Khurasan were preoccupied with tribal conflicts between the Yemeniand measurement.